Dangerous curves : action heroines, gender, fetishism, and popular culture - Brown, Jeffrey A., 1966- (Jackson : University Press of Mississippi, 2011)
Dangerous Curves: Action Heroines, Gender, Fetishism, and Popular Culture addresses the conflicted meanings associated with the figure of the action heroine as she has evolved in various media forms since the late 1980s. Jeffrey A. Brown discusses this immensely popular character type as an example of, and challenge to, existing theories about gender as a performance identity. Her assumption of heroic masculine traits combined with her sexualized physical depiction demonstrates the ambiguous nature of traditional gender expectations and indicates a growing awareness of more aggressive and violent roles for women.
Introduction : "where all women wear spandex and know Kung Fu" -- Gender and the action heroine : hardbodies and the point of no return -- Gender, sexuality, and toughness : the bad girls of action film and comic books -- Alias, fetishism, and Pygmalion fantasies -- "Play with me" : sexy cyborgs, game girls, and digital babes -- If looks could kill : power, revenge, and stripper movies -- "She can do anything!" : the action heroine and the modern (post-feminist) girl -- "Exotic beauties" : ethnicity and comic book superheroines -- Kinky vampires and action heroines -- When the action heroine looks -- Conclusion : wondering about Wonder Woman : action heroines as multi-fetish.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 25, 2023).
eBooks on EBSCOhost
Keywords: Bibel; Heroines in motion pictures; Heroines on television; Heroines in literature; Women in popular culture; Fetishism (Sexual behavior) on television; Fetishism (Sexual behavior) in motion pictures; Héroïnes au cinéma.; Héroïnes à la télévision.; Héroïnes dans la littérature.; Femmes dans la culture populaire; SOCIAL SCIENCE -- Women's Studies; SOCIAL SCIENCE -- Popular Culture; Comic books, strips, etc; Heroines in literature; Women heroes in motion pictures; Women in popular culture; Heldin; Geschlechterrolle; Frau; Popkultur; Comic; Massenkultur; Massenkultur; Comic; Frau; Film; Actionfilm; Heldin; Superheld; Geschlechterrolle; Frau; Pop-Kultur.; Comic; Electronic books; Criticism, interpretation, etc; Film criticism; Comics criticism; Critiques cinématographiques.; Critiques de bandes dessinées et de romans graphiques